How do we integrate skills and content in classics? An inquiry into students' use of sources. (February 2021) - Goodwin, Karl A; Quinlan, Kathleen M
Engagement with primary sources is a key feature of arts and humanities subjects, particularly classics and ancient history. Recent instructional trends emphasise integrating skills with content, particularly in the first year of higher education. We investigate how successfully first-year university students used a variety of sources in an integrated skills and content course, through analysis of 84 final essays. Most students used four to nine sources in a 1500 word essay, but only one type of ancient source. The findings express the need to move from debates about whether to integrate skills or not, to greater discuss how key discipline-specific skills are integrated into content-based courses. Cognitive apprenticeship theory, and a thematic approach used in museum education, are used to reflect on the findings and discuss how teachers might better support students in this key aspect of the discipline.